2004
DOI: 10.1136/pgmj.2004.019570
|View full text |Cite
|
Sign up to set email alerts
|

Management of traumatic brain injury: some current evidence and applications

Abstract: Traumatic brain injury remains a worldwide problem. Newer modalities in the management of such injuries include both drugs and therapeutic strategies. Continuing research in animal models has provided a better understanding of the pathophysiological processes that follow head injury, and this in turn has enabled workers to work on improved treatment targets. Although there are exciting and novel approaches emerging, there is no substitute for meticulous initial resuscitation. Additionally, some of the more wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 33 publications
0
30
0
4
Order By: Relevance
“…It is recognized as a leading cause of mortality and morbidity in young adults in industrialized countries (Fu and Tummala, 2005; Guha 2004; Vink and Nimmo, 2009). TBI is caused by both direct neural tissue damage and secondary (delayed) sequelae (reviewed by Fu and Tummala, 2005; Guha 2004; Jagannathan and Jagannathan, 2008; Vink and Nimmo, 2009). Primary injury is irreversible and leads to neuronal injury and vascular damage with immediate clinical effects.…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%
“…It is recognized as a leading cause of mortality and morbidity in young adults in industrialized countries (Fu and Tummala, 2005; Guha 2004; Vink and Nimmo, 2009). TBI is caused by both direct neural tissue damage and secondary (delayed) sequelae (reviewed by Fu and Tummala, 2005; Guha 2004; Jagannathan and Jagannathan, 2008; Vink and Nimmo, 2009). Primary injury is irreversible and leads to neuronal injury and vascular damage with immediate clinical effects.…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%
“…1 Glasgow Coma Scale score (GCS) and age are important prognostic indicators in patients with severe TBI (Hukkelhoven et al, 2003;Maas et al, 2007a). In all trials that were designed to investigate the effects of new medications for the treatment of severe TBI, patients aged over 65 years, as well as patients who had GCS scores <5, were excluded (Guha, 2004;Slieker et al, 2008). There are some observational studies that concluded that age over 65 years and GCS scores of 3 or 4 are both associated with poor outcomes (Tokutomi et al, 2008;Utomo et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…19,20 In addition, increased intracranial pressure, brain herniation, inflammation, and vascular compression occur. [21][22][23][24] Overall, these changes are reflected in hemodynamic and metabolic parameters, as well as in altered cellular morphology over time in brain tissue. The optical properties of the same can be quantified using the BeerLambert law and Mie scattering approximation.…”
Section: Introductionmentioning
confidence: 99%